Nursing intervention: Kinesio taping to reduce restless legs syndrome symptoms in patients undergoing hemodialysis - Anggit Prasetya; Agus Santosa; Jebul Suroso (Український Журнал Нефрології та Діалізу)
Restless legs syndrome (RLS) is a common neurological disorder affecting hemodialysis patients, significantly impacting their quality of life. While traditional treatments can provide relief, complementary interventions such as Kinesio taping (KT) may offer additional benefits. This study aimed to evaluate the effectiveness of KT in reducing RLS symptoms in patients undergoing hemodialysis.